Synthesis and Characterization of Zero-Valent Iron Using Polyphenols Extracted from Kepok Banana Peel (Musa paradisiaca Normalis) - Saul Panjaitan; Fera Kurniadewi; Setia Budi (Pusat Inovasi Sains, 2022)
This study aims to synthesize zero-valent iron (ZVI) with green-chemistry method. Synthesis was performed by reducing Fe2+ ion using polyphenol extract. The extract was obtained from banana peel that abundant in Indonesia and contain high of polyphenols. Synthesis of ZVI was carried out by reacting polyphenol extract to FeSO4 solution with different composition 1:4, 2:3, 1:1, 3:2, 4:1, and 4.5:0.5. The gas chromatography-mass spectroscopy spectrum confirmed the existence of polyphenols in the banana feel extract from the observed peaks assigned to 2-methoxy-4-vinylphenol, 4 methoxy-2-vinylphenol, and 2-methoxy-5-vinylphenol. Based on the atomic absorbtion spectroscopy data, the best composition for ZVI’s synthesis was 4:1 (polyphenol extract : FeSO4 solution). The fourier transform infrared spectroscopy spectrum shows that there was –OH group indicating a present of polyphenol in the synthesized ZVI. The energy dispersive X-ray spectroscopy shows that the sample contain of Fe, C, O, S, Ca, Cu, and Na. The X-ray diffraction analysis exhibit crystalline phase of a simple cubic structure of the synthesized ZVI. This results shows that the ZVI was successfully synthesized using environmentally benign reducing agent extracted from the banana peel.